Crack Analysis Due to Fatigue Load During Subsea Pipeline Installation - Franciscus Ventus Nagoya; Winarto (International Journal of Marine Engineering Innovation and Research, 2022)
Most of the subsea pipelines in Indonesia are installed using the S-Lay method with the pipelay barges equipped with mooring spreads, tensioners, and stinger. During the subsea pipeline installation, static loads occur due to the pipeline configuration from the firing line of the pipelay barge up to the seabed. The pipe will experience axial tension and bending moment in two critical areas: overbend and sagbend. In addition, fatigue loads occur during subsea pipeline installation due to environmental loads (i.e., currents and waves). Defects that are found after welding will grow due to these fatigue loads. Crack analysis with a fracture mechanic approach known as Engineering Critical Assessment (ECA) is carried out by considering the fatigue load due to significant wave height variations for 0.5m, 1.0m, and 1.8m. BS 7910 is used as a standard reference to determine the allowable defects criteria for external and internal flaws. The depth of the defect (a) is simulated from a depth of 1mm – 3mm. The analysis found that the allowable defect length is decreased by 12.7% - 25.0% from a significant wave height of 0.5m to 1.8m for the external surface flaw. While for an internal surface flaw, the allowable defect length is decreased by 5.9% - 13.6% from a significant wave height of 0.5m to 1.8m. These results can be used as a basis for subsea pipeline installation contractors to perform fatigue load sensitivity and optimize the allowable defects based on the actual wave load at the site.